PENGHAMBATAN AKTIVITAS ENZIM α-GLUKOSIDASE DARI EKSTRAK AIR TANAMAN RARU (Vatica pauciflora) SECARA IN VITRO - eris septiana; wiwi winarti; partomuan simanjuntak (Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
Diabetes mellitus is a metabolic disorder that leading the blood sugar levels become higher than normal. In Indonesia, one of the plants that traditionally used to cure hyperglycemic is raru plant (Vatica pauciflora). The objectives of this research was to investigate α-glucosidase inhibitory activity from stem bark, root, and leaf of raru plant. Extraction of stem bark, root, and leaf was conducted with reflux at 70 °C by using water as a solvent. In vitro anti-diabetic activity was tested using the method of α-glucosidase inhibition. The results show that water extracts of raru’s stem bark, root, and leaf have α-glucosidase inhibitory activity. The stem bark water extract has the highest activity than leaf and root with IC50 values were 13.53, 16.96, and 41.91 ppm respectively. All extracts is categorized as active in inhibiting the activity of α-glucosidase enzyme by having IC50≤100 ppm. The results obtain in this research clearly indicate a promising potential as anti-diabetic properties of raru plant.